Jewish youth and identity in postwar France : rebuilding family and nation - Doron, Daniella (The modern Jewish experience, 2015)
"Their children? Our children!" Holocaust memory in postwar France -- "A drama of faith and family": custody disputes in postwar France -- Notre vie en commune: the family versus the children's home -- The homes of hope? Trauma, universal victimhood, and universalism -- From competition to cooperation: redefining Jewish identities